The Mediating Role of Familial Support and Religiosity on Youths' Mental Health and Illicit Drug Use: A Path Analysis. - Ismail, Rozmi; Shukor, Md Shafiin; Ganasegeran, Kurubaran; Manaf, Mohd Rizal Abdul (International Journal of Mental Health & Addiction, 2025)
Although the extent of illicit drug use (IDU) among youths is alarming, there are only a handful of mechanisms that explain the pathway-interactions between IDU and mental health (MH). As such, the present study examines the mediating effects of familial support (FS) and religiosity (R) on IDU among Malaysian youths. Between January 2020 and July 2021, a nationwide interviewer administered face-to-face cross-sectional survey was conducted among 9818 youths aged 15–40, who were selected via multi-stage complex sampling. The validated local versions of the depression, anxiety, and stress scales (DASS-21); alcohol, smoking and substance involvement screening test (ASSIST); the multidimensional scale of perceived social support; and the religious commitment inventory-10 were used to assess the respondents' perceived MH status, IDU, FS, and R. Generalised structural equation modelling (GSEM) was then used to examine the intricate correlations between the variables via Stata version 14.0. The lifetime prevalence of IDU among Malaysian youths was 0.7% for opiates and 2.5% for cannabis, while the prevalence of ongoing IDU was 0.3% for opiates and 1.5% for cannabis. The direct effects logit and mediation models revealed significant correlations between perceived anxiety (path coefficient (β) = 0.114, p < 0.001), depression (β = 0.201, p < 0.001), stress/pressure (β = 0.067, p < 0.001) and IDU. Familial support (FS) (β = -0.097, p < 0.001) and R (β = -0.042, p < 0.001) were found to prevent IDU. More specifically, FS mediated anxiety, depression, and IDU while strong R discouraged IDU and provide depressed or stressed youths alternative coping mechanisms. Therefore, FS and R are important potential buffers against the many MH challenges associated with IDU. As such, interventions that strengthen FS and promote genuine R must be considered to mitigate IDU among youths.